(untitled) (Itinera, 2017)
Soaked wet under the rain of a thunderstorm or shivering in the cold: when confronted to weather phenomenons by playwrights, characters are no longer defined by their sole ability to speak. Intervention of meteorological parameters engages the passive side of the sense of touch, hence resulting in what we would qualify as a dramatic writing of the skin. Through the examples of The Blind by Maurice Maeterlinck (1890) and Uncle Vanya by Anton Chekhov (1897), we postulate that this engagement of senses cannot be limited to a simple concession to realism. This writing of the skin contributes to the recreation of unity in drama at the turn of the century, when the action is no longer its structural principle, and discretely remedies the drama of incommunicability.